INNOVATION IN MEDIEVAL MUSIC: मध्यकालीन संगीत में नवाचार - Mahobia, Usha (International Journal of Research -GRANTHAALAYAH, 2015)
The tradition of music in India has been going on since ancient times. The early Hindu rulers gave shelter to the musicians in their court, but the staunch Muslim rulers looked at the music with religious sentiments, meaning music is forbidden love according to Islamic rules, but indirectly the sweet voice is also praised in the Quran. The Khalifa himself has praised the sweet gorge, Abumusa Asari used to recite the Quran very sweetly. Thus music remained prohibited despite being prohibited. भारत वर्ष में संगीत की परम्परा प्राचीन काल से चली आ रही है। प्रारभिंक हिन्दू शासकों ने अपने दरबार में संगीतकारो को आश्रय दिया किन्तु कट्टर मुसलमान शासकों ने संगीत को धार्मिक भावनाओ के कारण हेय दृष्टि से देखा अर्थात् इस्लामी नियमानुसार संगीत प्रेम निषेध है किन्तु अप्रत्यक्ष रूप से कुरान में भी मीठी आवाज की प्रशंसा की गई है। स्वयं खलीफा ने मधुर कण्ठ की तारीफ की है, अबूमूसा असारी कुरान का पाठ बडे ही मधुर स्वर में किया करता था । इस प्रकार संगीत निषिद्ध होते हुये भी प्रशंसा का पात्र बना रहा ।